Medical student research productivity and scholarly impact: A 20-year bibliometric comparison with medical residents - Christian J. Hausner; Michelle Yi; Meet S. Patel; Jack T. Franchino; Charles S. Day (PLoS ONE, 2026)
Research experience during medical school is widely recognized as a valuable component of medical education and an increasingly emphasized aspect of residency applications. However, growing research productivity among medical students has led to concerns regarding the quality and translatability of the research. To assess the impact of medical student-authored research, we compared it with resident-authored research across a 20-year period using a cohort study and bibliometric analysis of 1,443 student-authored and 5,365 resident-authored PubMed-indexed articles published from 2003 to 2023. NIH iCite Relative Citation Ratio (RCR), a field-and-time normalized measure of article influence, was utilized to quantify research quality. We identified publications authored by medical students or residents using standardized affiliation-based queries. Primary outcomes included publication volume, citation count, and RCR. Secondary analyses compared article impact by study design, specialty, and geographic origin. We found that medical student publications increased 15-fold from 2003 to 2023 (from <10 to ~150 per year). Moreover, despite publishing less overall volume than residents, medical student publications demonstrated greater scholarly impact than medical resident publications over this period (RCR 0.47 vs 0.26; p = 0.02). By 2023, the median relative citation ratio of medical student-authored publications was 0.8, approaching the benchmark for a median NIH-funded article (RCR = 1.0). Medical students published nearly twice as many articles in surgical specialties as medical specialties but with comparable median RCRs (0.44 vs 0.47; p = 0.73). Additionally, the median RCR of both U.S. and international medical student publications significantly increased over the past two decades. In conclusion, medical student research output has grown substantially, and our analysis demonstrates that medical students contribute impactful research that is frequently cited and built upon. These findings underscore the importance of student-led scholarship and continued support for medical student research opportunities. To facilitate future benchmarking of trainee research, we also provide ImpactLens : https://impactlensgit.netlify.app/ .